2023
DOI: 10.1002/chem.202300021
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Densification of Mo/Mg Co‐Doped Apatite‐type Lanthanum Silicate Electrolytes with Enhanced Ionic Conductivity

Abstract: Apatite-type lanthanum silicate (LSO) electrolyte is one of the most promising candidates for developing intermediate-temperature solid oxide electrolysis cells and solid oxide full cells (IT-SOECs and SOFCs) due to its stability and low activation energy. However, the LSO electrolyte still suffers from unsatisfied ionic conductivity and low relative density. Herein, a new co-doped method is reported to prepare highly purified polycrystalline powders of MgÀ Mo codoped LSO (Mg/Mo-LSO) electrolytes with high exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The difference of the doped cations, especially the ionic radius, results in the difference of cell distortion and restraining O 2À , and then LSO conductivity changes accordingly. Finally, Li et al [71] evaluated the conductivity of co-doped LSO with Mg 2 + and Mo 6 + on Si-site. Compared to the pure LSO, the conductivity of Mg/Mo-LSO was significantly enhanced.…”
Section: Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The difference of the doped cations, especially the ionic radius, results in the difference of cell distortion and restraining O 2À , and then LSO conductivity changes accordingly. Finally, Li et al [71] evaluated the conductivity of co-doped LSO with Mg 2 + and Mo 6 + on Si-site. Compared to the pure LSO, the conductivity of Mg/Mo-LSO was significantly enhanced.…”
Section: Conductivitymentioning
confidence: 99%
“…Co-doped LSO with Mg 2 + and Mo 6 + on Si-site can be readily densified at a relatively low sintering temperature of ~1500 °C, the relative density reaching 98 %, without any sintering aids or additives. [71] On the other hand, Celerier et al [73] reported the use of acidcatalyzed silica sol with TEOS and La(NO 3 ) 3 as precursors for the gel formation to prepare directly LSO powder. These powders can be used directly to form ceramics, allowing a decrease of the sintering temperature of more than 200 °C.…”
Section: Sinteringmentioning
confidence: 99%
“…33 Co-doping the common solid oxide composites with aliovalent transition metal cations is a new approach to improve the densification properties and ionic conductivity of the resulting polycrystalline electrolytes. 34 Considering the protection for the metal support in the fabrication process, the study of sintering behaviour in an inert atmosphere for doping ceria-based composites is necessary. Also, the physicochemical and electrochemical properties for multi-doped ceria-based This journal is © The Royal Society of Chemistry and IChemE 2023 composites were rarely reported.…”
Section: J = Mc∇μmentioning
confidence: 99%